Alginate Oligosaccharide Promoted the Nutrient Uptake and Growth of Cucumber Seedlings Under Suboptimal Temperature Conditions - Xu Guo; Yun Li; Kai Fan; Lingru Guo; Yongzhao Yang; Chunming Cheng; Leiping Hou; Yanxiu Miao; Meihua Sun; Yaling Li; Longqiang Bai (Horticulturae)
Due to its sensitivity to cold temperatures, cucumber growth is substantially constrained by suboptimal temperature stress in northern China’s off-season production systems. Suboptimal temperatures severely repress the nutrient absorption, growth, and yield formation of vegetables in solar greenhouses during winter and early spring in China. Alginate oligosaccharides (AOSs) are anionic acidic polysaccharides derived from brown algae, known for promoting plant growth and alleviating abiotic stress. In this study, we aimed to investigate the effects of different nutrient solution concentrations combined with AOS on the growth and nutrient uptake of cucumber seedlings under suboptimal temperatures (15/8 °C, day/night). Potted ‘Jinchun 4’ cucumber seedlings grown in coconut coir were treated with 0.5×, 1.0×, or 1.5× strength of Hoagland solution alone (N0.5, N1, N1.5), or with 30 mg·L−1 AOS (A0.5, A1, A1.5). The results showed that the growth attributes and nitrogen (N) accumulation of cucumber plants of N1 and N1.5 were significantly higher than those of N0.5. Additionally, plants of A0.5 exhibited significantly higher plant height, chlorophyll a content, root surface area, root volume, root vitality, N metabolism enzyme (NR, GDH, GS) activities, and N accumulation, than those under N0.5, N1, or N1.5. Moreover, compared to A0.5, the net photosynthetic rate, total root length, root surface area, root N content, leaf nitrate reductase activity, root glutamate dehydrogenase activity, and N accumulation of A1 and A1.5 were significantly higher than those of A0.5. Correlation analysis revealed strong linkages between root morphology traits and tissue N content. In summary, under suboptimal temperature conditions, the application of AOS improved cucumber seedlings’ nutrient absorption and growth more efficiently than merely raising nutrient levels, as it enhanced root surface area, root vitality, and N metabolic enzyme activities.